Respuesta :
Option A: [tex](x+3)^2+(y+2)^2=4[/tex] is the equation of the circle
Explanation:
The equation of the circle is [tex]x^{2} +y^2+6x+4y+10=1[/tex]
We need to write the equation of the circle in standard form.
Let us subtract 10 from both sides of the equation.
Thus, we have,
[tex]x^{2} +y^2+6x+4y=-9[/tex]
Grouping the terms,we have,
[tex](x^{2} +6x)+(y^2+4y)=-9[/tex]
Now, we shall complete the square, let us add and subtract the equation by 9 to write the term [tex]\left(x^{2}+6 x\right)[/tex] in the form of [tex](a+b)^2[/tex]
Thus, we have,
[tex](x^{2} +6x+9-9)+(y^2+4y)=-9[/tex]
Simplifying, we get,
[tex](x^{2} +6x+9)+(y^2+4y)=-9+9[/tex]
[tex](x+3)^2+(y^2+4y)=0[/tex]
Similarly, we shall complete the square for the term [tex]\left(y^{2}+4 y\right)[/tex] in the form of [tex](a+b)^2[/tex]
Thus, we have,
[tex](x+3)^2+(y^2+4y+4-4)=0[/tex]
Simplifying, we get,
[tex](x+3)^2+(y^2+4y+4)=4[/tex]
[tex](x+3)^2+(y+2)^2=4[/tex]
Thus, the equation of the circle in standard form is [tex](x+3)^2+(y+2)^2=4[/tex]
Hence, Option A is the correct answer.